The main obstacles to firms' growth in Senegal: Implications for the long run - Mathilde Maurel; Majda Seghir (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Productivity gains are the prime engine of economic growth. This paper uses a rich amount of firms' accounting information from the Single Information Collecting Centre in Senegal over the period 1998-2011. To investigate the two main obstacles to growth, poor education and poor access to electricity supply, we aggregate the firms' data at the sectoral level. Our findings corroborate the conclusion of a recent report by the African Development Bank suggesting the importance of primary and vocational education. Another key conclusion drawn in the AfDB report is that the main obstacle to production is the poor access to electricity and the low quality of infrastructure. Based upon a World Bank indicator of access and some strong but reasonable assumptions regarding the sectoral demand for electricity, we estimate the impact of the electricity access on firms' total factor productivity.
Keywords: O11; O44; C33; 330; productivity dynamics; total factor productivity; education; electricity supply